Acute myocardial infarction with normal electrocardiogram and biomarkers of cardiac injury: A case report - Zha, Ke‐Lan; Wen Chen; Qiang Ye (Annals of noninvasive electrocardiology, 2023)
Patients with AMI usually present with the specific changes for electrocardiogram (ECG) and biomarkers of cardiac injury. Here, we present a rare case with chest pain and normal ECG and biomarkers of cardiac injury. Emergent coronary angiography revealed an occlusion of proximal left anterior descending coronary artery. The patient was diagnosed with AMI, and his symptom relieved after implantation of drug‐eluting stents. Caution should be exercised for the exclusion of AMI in patients with chest pain and both normal ECG and biomarkers of cardiac injury. AMI with normal ECG and biomarkers of cardiac injury is exceedingly rare. The clinical manifestations of AMI were complex and varied, especially that the patients with atypical AMI were increasing in clinical practice. Caution should be exercised to exclude AMI in patients with chest pain and both normal ECG and biomarkers of cardiac injury.